Prevalence of depression in China during the early stage of the COVID-19 pandemic: a cross-sectional study in an online survey sample - Liu, Weina; Yu, Fengyun; Geldsetzer, Pascal; Yang, Juntao; Wang, Zhuoran; Golden, Todd; Jiao, Lirui; Chen, Qiushi; Liu, Haitao; Wu, Peixin; Wang, Chen; Bärnighausen, Till; et al. (BMJ open, 2022)
Objectives We aimed to determine (1) the prevalence of depression during the COVID-19 pandemic among Chinese adults and (2) how depression prevalence varied by province and sociodemographic characteristics. - Design Cross-sectional study. - Setting National online survey in China. - Participants We conducted a cross-sectional online survey among adults registered with the survey company KuRunData from 8 May 2020 to 8 June 2020. We aimed to recruit 300-360 adults per province (n=14 493), with a similar distribution by sex and rural-urban residency as the general population within each of these provinces. - Primary outcome Participants completed the Patient Health Questionaire-9 (PHQ-9). We calculated the prevalence of depression (defined as a PHQ-9 score ≥10) nationally and separately for each province. - Analysis Covariate-unadjusted and covariate-adjusted logistic regression models were used to examine how the prevalence of depression varied by adults’ sociodemographic characteristics. All analyses used survey sampling weights. - Results The survey was initiated by 14 493 participants, with 10 000 completing all survey questions and included in the analysis. The prevalence of depression in the national sample was 6.3% (95% CI 5.7% to 6.8%). A higher odds of depression was associated with living in an urban area (OR 1.50; 95% CI 1.18 to 1.90) and working as a nurse (OR 3.06; 95% CI 1.41 to 6.66). A lower odds of depression was associated with participants who had accurate knowledge of COVID-19 transmission prevention actions (OR 0.71; 95% CI 0.51 to 0.98), the knowledge that saliva is a main transmission route (OR 0.80; 95% CI 0.64 to 0.99) and awareness of COVID-19 symptoms (OR, 0.82; 95% CI 0.68 to 1.00). - Conclusion Around one in 20 adults in our online survey sample had a PHQ-9 score suggestive of depression. Interventions and policies to prevent and treat depression during the COVID-19 pandemic in China may be particularly needed for nurses and those living in urban areas.